2021
DOI: 10.1038/s41598-021-03488-1
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity and ecosystem functions depend on environmental conditions and resources rather than the geodiversity of a tropical biodiversity hotspot

Abstract: Biodiversity and ecosystem functions are highly threatened by global change. It has been proposed that geodiversity can be used as an easy-to-measure surrogate of biodiversity to guide conservation management. However, so far, there is mixed evidence to what extent geodiversity can predict biodiversity and ecosystem functions at the regional scale relevant for conservation planning. Here, we analyse how geodiversity computed as a compound index is suited to predict the diversity of four taxa and associated eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 87 publications
(123 reference statements)
1
14
0
Order By: Relevance
“…These ecosystems, despite being relatively close to each other, seem to be very particular in their insect composition. For instance, in this region the biodiversity of ants and a predation function associated with them was better explained by habitat conditions than by abiotic variables in an altitudinal gradient (Wallis et al 2021), andThormann et al (2018) showed that species composition of leaf beetles clearly changed between Andean forests and rainforests even when they were connected and part of the same mountain range. SCVI reached nearly 100 at some of the reserves in dry forests and rainforests, meaning that nearly 100% of individuals in those samples were represented by only one species.…”
Section: Discussionmentioning
confidence: 88%
“…These ecosystems, despite being relatively close to each other, seem to be very particular in their insect composition. For instance, in this region the biodiversity of ants and a predation function associated with them was better explained by habitat conditions than by abiotic variables in an altitudinal gradient (Wallis et al 2021), andThormann et al (2018) showed that species composition of leaf beetles clearly changed between Andean forests and rainforests even when they were connected and part of the same mountain range. SCVI reached nearly 100 at some of the reserves in dry forests and rainforests, meaning that nearly 100% of individuals in those samples were represented by only one species.…”
Section: Discussionmentioning
confidence: 88%
“…That is, species turnover between elevations was significantly higher between plots differing in environmental conditions than between plots with similar environmental conditions. Environmental heterogeneity has been described as a dominant driver of biodiversity for many taxa in the tropical montane forest of Ecuador (Wallis et al 2021). In line with our findings, beta‐diversity patterns in Andean forests are driven by environmental heterogeneity (Arellano et al 2016b).…”
Section: Discussionmentioning
confidence: 99%
“…Tropical montane forests offer a unique, natural laboratory to investigate the extraordinary diversity of plants due to high environmental heterogeneity and broad environmental gradients (Malhi et al 2010, Arellano et al 2016b). In particular, elevational gradients are very useful to compare processes operating at local and regional scales (Arellano et al 2016a), as environmental conditions and biotic pressures differ within and between elevations and may contribute to the high diversity of plants in tropical mountains (Arellano et al 2017, Sam et al 2020, Wallis et al 2021). Yet more studies on beta‐diversity are required to better understand processes of community assembly in seedling communities (Arellano et al 2016a, Conradi and Kollmann 2016, Gianuca et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Based on our experience, discussions and peer‐review feedback, one of the most common misconceptions is that geodiversity is perceived either too broadly or too narrowly (Figure 3). For instance, geodiversity is sometimes equated with the full range of environmental heterogeneity, or it includes biotic components (Wallis et al., 2022) or climate variation (Parks & Mulligan, 2010; Zarnetske et al., 2019). On the other hand, geodiversity is sometimes considered as a synonym for a single abiotic variable or its heterogeneity (such as a single geological feature or topographical heterogeneity; Crisp et al., 2023) or is thought to cover only the subsurface (van Ree & van Beukering, 2016).…”
Section: Current Issues and Misconceptionsmentioning
confidence: 99%